INOVASI UBI UNGU MENJADI DONUT SEBAGAI KREATIVITAS PRODUK LOKAL DI KELURAHAN MANGUNSARI, KECAMATAN GUNUNGPATI, KOTA SEMARANG - Nurchayati, Nurchayati; Muchayatin, Muchayatin; Parju, Parju; Suyati, Sri; Setyobudi, Setyobudi; Sulistyani, Sulistyani; Aminah, Siti; Riyanto, Joko; Musprihadi, Ribut (MAJU : Indonesian Journal of Community Empowerment, 2025)
This community service program aims to empower the people of Mangunsari Village, Gunungpati District, Semarang City through purple sweet potato-based donut innovation. The main problem is the low added value of purple sweet potatoes, which are only sold raw, and limited knowledge of processed product diversification. The implementation method included training in donut making, packaging, branding, and marketing management for 25 participants. Results showed a significant increase in participant knowledge from 38% to 87%, with 92% of participants able to produce high-quality donuts. The optimal formulation using a 37.5% substitution of purple sweet potato puree resulted in an organoleptic acceptance level of 84-88%. Value-added analysis showed a 1,025% increase in economic value with a profit margin of 260%. The "Sate Donat Mini 17" business group was formed, with 48% of participants actively producing, generating additional income of IDR 1.8-3.5 million per month. The program has had a positive impact on community economic empowerment and increasing the added value of local commodities. Keywords: Community Empowerment, Purple Sweet Potato, Product Innovation, Added Value, Entrepreneurship